Gravity currents with temperature-dependent viscosity - King, John R.; Riley, David S.; Sansom, Ahmos (Computer Assisted Methods in Engineering and Science, 2023)
The spreading of fluid under gravity occurs in both nature and man-made situations and has been the subject of many previous studies. Considerably less attention has been paid to cases in which there is a strong thermal coupling influencing the flow. In this paper, simple models of the spreading of materials with temperature-dependent viscosity are presented and features that are commonly seen in experiments, such as plateauing and fingering, are shown to result. A model which includes latent heat effects is also briefly outlined.